Integrated Computer Systems. Enterprise Resource Planning (E.R.P.) - TRANĂ, Dan Mircea (Annals of Spiru Haret University. Economic Series, 2014)
At the beginning of the XXI century society, knowledge based society, the management of economic organizations can only be achieved through optimal IT systems. They can be seen as an extension of increasingly complex information systems and provide effective leadership only if they are integrated in the economic system of the organization. We have previously shown some of the features that recommend integrated IT systems to be controlled and used, as well as main principles for building the integrated computer systems, strategies that can be applied in the designing of this type of IT system. Advantages of management integrated IT systems can be best supported by examples, and therefore we intend to present a special category, but increasingly used, of integrated IT systems: Enterprise Resource Planning (ERP). They are “distributed IT systems based on client / server and developed for the processing of transactions and facilitating the integration of business processes with suppliers, customers and other business partners.”